Effect of Calcination Temperature and Heating Rate on Zinc Oxide (ZnO) Synthesis Toward Antibacterial Properties - Soni Setiadji; Vianti Aprilia (Jurnal Kimia Sains dan Aplikasi, 2025)
The increasing resistance of pathogenic bacteria to conventional antibacterial agents poses a significant challenge to global health, driving the need for alternative antibacterial materials with minimal resistance potential. Zinc oxide (ZnO) has gained attention for its antibacterial properties, attributed to its ability to generate reactive oxygen species (ROS), release Zn2+ ions, and disrupt bacterial cell membranes. In this study, ZnO was synthesized via thermal decomposition of zinc acetate dihydrate, with different calcination temperatures and heating rates. The structural and morphological characteristics of ZnO were analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM), revealing that higher calcination temperatures increased crystallinity while heating rates influenced particle morphology. Antibacterial tests against Staphylococcus aureus and Escherichia coli showed that ZnO exhibited stronger antibacterial activity against S. aureus. The results also indicated that higher calcination temperatures reduced antibacterial efficacy, whereas higher heating rates enhanced bacterial inhibition. Notably, ZnO synthesized at 500°C with a heating rate of 5°C/min demonstrated the highest antibacterial performance, which correlated with its lower crystallinity and rod-like morphology. These findings emphasize the importance of controlling synthesis parameters to optimize ZnO properties for biomedical applications.